Analysis of Global Citizenship Education (GCE): Challenges and Opportunities of Realizing Global Citizenship Education - Rodiah Harahap; Panggih Nur Adi; Aina Nurdiyanti; Siti Zahara Saragih (Universitas of Muhammadiyah Makassar, 2024)
One of the main problems in this research is the increasingly fierce competition in various fields. In order to compete and develop, knowledge and skills are needed that are in line with global demands. Citizenship education focuses on the era of globalization and global citizenship. This is due to the fact that societies around the world are interconnected, and citizenship education requires a deeper understanding of global citizenship. Global Citizenship Education (GCE), which combines elements of education and global citizenship, has become an important topic in educational literature. This research method uses a qualitative descriptive approach. This type of research uses Library Research. In general, according to research from this journal, there are at least three global dimensions that will continue to develop and benefit global citizens, especially young citizens.